Unveiling the role of disulfidptosis-related genes in the pathogenesis of non-alcoholic fatty liver disease - Luo, Xiaohua; Guo, Junjie; Deng, Hongbo; He, Zhiyong; Wen, Yifan; Si, Zhongzhou; Li, Jiequn (Frontiers in Immunology, 2024)
Backgrounds: Non-alcoholic fatty liver disease (NAFLD) presents as a common liver disease characterized by an indistinct pathogenesis. Disulfidptosis is a recently identified mode of cell death. This study aimed to investigate the potential role of disulfidptosis-related genes (DRGs) in the pathogenesis of NAFLD.Methods: Gene expression profiles were obtained from the bulk RNA dataset GSE126848 and the single-cell RNA dataset GSE136103, both associated with NAFLD. Our study assessed the expression of DRGs in NAFLD and normal tissues. Weighted gene co-expression network analysis (WGCNA) and differential expression analysis were employed to identify the key NAFLD-specific differentially expressed DRGs (DE-DRGs). To explore the biological functions and immune regulatory roles of these key DE-DRGs, we conducted immune infiltration analysis, functional enrichment analysis, consensus clustering analysis, and single-cell differential state analysis. Finally, we validated the expression and biological functions of DRGs in NAFLD patients using histology and RNA-sequencing transcriptomic assays with human liver tissue samples.Results: Through the intersection of WGCNA, differentially expressed genes, and DRGs, two key DE-DRGs (DSTN and MYL6) were identified. Immune infiltration analysis indicated a higher proportion of macrophages, T cells, and resting dendritic cells in NAFLD compared to control liver samples. Based on the key DE-DRGs, Two disulfidptosis clusters were defined in GSE126848. Cluster 1, with higher expression of the key DE-DRGs, exhibited increased immune infiltration abundance and was closely associated with oxidative stress and immune regulation compared to cluster 2. High-resolution analysis of mononuclear phagocytes highlighted the potential role of MYL6 in intrahepatic M1 phenotype Kupffer cells in NAFLD patients. Our transcriptome data revealed that the expression levels of the majority of DRGs were significantly increased in NAFLD patients. NAFLD patients exhibit elevated MYL6 correlating with inflammation, oxidative stress, and disease severity, offering promising diagnostic specificity.Conclusion: This comprehensive study provides evidence for the association between NAFLD and disulfidptosis, identifying potential target genes and pathways in NAFLD. The identification of MYL6 as a possible treatment target for NAFLD provided a novel understanding of the disease's development.